2008
DOI: 10.1002/eji.200737974
|View full text |Cite
|
Sign up to set email alerts
|

Development of CTL memory despite arrested clonal expansion

Abstract: Activation of a cytotoxic T lymphocyte (CTL) response in an antigen-exposed lymph node involves a great diversity of encounters between naive CTL and APC that differ in both duration and quality. This broad spectrum of priming events instigates a complex blend of CTL developmental pathways. Using an experimental system that allows tight control over CTL priming, we have singled out defined priming events and analyzed the impact of the resulting instructional program on the effector and memory phases of the CTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Prior work had demonstrated that a 20-h in vitro encounter with these APCs empowered naive OT-I cells to vigorously proliferate in vivo upon transfer to naive syngeneic recipient (15). Furthermore, these T cells were shown to develop into long-lived memory cells, capable of clonal expansion and protective effector function in response to secondary Ag encounter (16). Importantly, progression of the 20 h primed OT-I T cells through primary expansion, contraction, and memory phases required neither in vivo exposure to Ag nor the context of an inflamed, congested lymph node.…”
Section: Resultsmentioning
confidence: 99%
“…Prior work had demonstrated that a 20-h in vitro encounter with these APCs empowered naive OT-I cells to vigorously proliferate in vivo upon transfer to naive syngeneic recipient (15). Furthermore, these T cells were shown to develop into long-lived memory cells, capable of clonal expansion and protective effector function in response to secondary Ag encounter (16). Importantly, progression of the 20 h primed OT-I T cells through primary expansion, contraction, and memory phases required neither in vivo exposure to Ag nor the context of an inflamed, congested lymph node.…”
Section: Resultsmentioning
confidence: 99%
“…20 In fact, T cells protect the health of an organism by mounting a well-orchestrated immune response consisting of proliferation effector cell differentiation, contraction and induction of cytotoxic T lymphocytes that kill viral infected cells. 21 In general, effector CD8+ T cells control infection through cytotoxic activity and the secretion of IFN-γ and TNF-α. 22 Moreover, CTL plays a major role in adaptive immunity to viral infections such as HIV-1.…”
mentioning
confidence: 99%
“…CTLs can persist for a long time and acquire memory function even under suboptimal stimulation conditions (42). Similarly, in our LCre-GFPOA mice, antigen presentation by resting LCs without additional co-stimulation was sufficient to prime endogenous CTL, and to develop effector function.…”
Section: Resultsmentioning
confidence: 99%